The Development of Tas Lisa Learning Media to Enhance Early Childhood Beginning Reading Skills - Helni Widayani; Sri Watini; Chandra Apriyansyah (Journal of Scientific Research, Education, and Technology (JSRET), 2026)
This study aims to develop TAS LISA learning media (Tas Literasi Anak Sederhana dan Atraktif) using a Research and Development (R&D) approach to improve the beginning reading skills of early childhood learners. The study was motivated by the low level of beginning reading ability among kindergarten children, particularly in recognizing letters, associating letters with sounds, and reading simple syllables and words. In addition, the literacy learning media used in classrooms are generally conventional and provide limited opportunities for concrete, interactive learning experiences that align with the developmental characteristics of young children. Therefore, an innovative learning medium developed through a systematic research and development process is needed. This study employed an R&D method consisting of several stages: analysis, data collection, product design, design validation by material and media experts, design revision, product trial, product revision, usage trial, and final product revision. The research subjects were 20 children from Group B in a kindergarten. Data were collected through observation, interviews, and expert validation questionnaires. Data analysis used quantitative descriptive methods to determine product feasibility and improvement in children's beginning reading skills, and qualitative descriptive analysis to describe the development process and children's responses to the media. The results indicate that the TAS LISA learning media is feasible based on expert validation and effective in improving children's beginning reading abilities, including letter recognition, syllable reading, and simple word reading.